Save our planet for the next generation - Abd Razak, Dzulkifli (2006)
RESEARCHERS and practitioners from the region converged on Universiti Sains Malaysia, Penang for a conference on Education for Sustainable Development (EfSD) last week. Sponsored by the Association of Southeast Asian Institutions of Higher Learning, the conference reiterated Asean's Vision 2020 for a clean and green region with fully established mechanisms for sustainable development. It also aims to protect the region's environment, the sustainability of its natural resources and the high quality of life of its people. Towards this end, Asean has put in place a number of plansdirected at tackling environmental issues in the region, as reflected in several ministerial declarations. These include the Manila Declaration on the Asean Environment (1981). Bangkok Declaration on the Asean Environment (1984), Singapore Resolution on Environment and Development (1992), Bandar Seri Begawan Resolution on Environment and Development (1994) and the Kota Kinabalu Resolution on the Environment (2000).